Penerapan Irigasi Tetes Emiter Tali Dengan Bebagai Selang Waktu Irigasi Pada Tanaman Semangka - Muhammad Idrus Idrus; Surya Surya (Jurnal Penelitian Pertanian Terapan, 2019)
The objectives of the research were (1) To know watermelon yield and irrigation water productivity of watermelon by used drip irrigation with nylon rope emitter on various time irrigation intervals, (2) To determined the good time irrigation interval for watermelon production by using the drip irrigation with nylon rope emitter. The research was conducted at the research field with four-time irrigation intervals were 1,2,3, and 4 days of time irrigation interval. The research was arranged in Completely Randomized Block Design. The result of the research showed that the time irrigation interval was not significantly affected yield and irrigation water productivity of watermelon. The soil moisture in the root zone at 30 cm depth of 23,23—23,88% before irrigation still in range of the available soil moisture content for plants. The average of watermelon yield and irrigation water productivity of watermelon were 5,07—5,45 kg/plant and 115,15—123,79 kg/m3. The good time interval of irrigation for watermelon production by using drip irrigation with rope emitter was 4 days time interval of irrigation.